2013
DOI: 10.1002/jgm.2701
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal virus inoculation into the scala media achieved extensive expression of exogenous green fluorescent protein in the inner ear and preserved auditory brainstem response thresholds

Abstract: Viral inoculation and expression in the inner ear for the restoration of hearing must not damage cochlear function. Using normal hearing mice as a model, we have achieved this necessary step, which is required for the treatment of many types of congenital deafness that require early intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 38 publications
4
32
0
Order By: Relevance
“…Several delivery strategies have been developed that access the cochlear fluids directly from that portion of the cochlear basal turn facing the middle-ear space. These approaches include: (1) a cochleostomy into either scala tympani or scala media1718224142, (2) injection through the round window membrane5172043, (3) or injection onto the surface of the round window, with or without manipulations to increase penetration38444546. The approach to the posterior canal differs in that the access is not through the middle ear22232425.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several delivery strategies have been developed that access the cochlear fluids directly from that portion of the cochlear basal turn facing the middle-ear space. These approaches include: (1) a cochleostomy into either scala tympani or scala media1718224142, (2) injection through the round window membrane5172043, (3) or injection onto the surface of the round window, with or without manipulations to increase penetration38444546. The approach to the posterior canal differs in that the access is not through the middle ear22232425.…”
Section: Discussionmentioning
confidence: 99%
“…Although approaches through the middle ear may be practical in human, where the relevant structures are relatively large, the middle and inner ear spaces in mouse are so small, and the inner ear so delicate, that the surgical access to, and/or injection into, the cochlear fluids seems to unavoidably cause cochlear damage2161722, unless injections are made prior to postnatal day 542. Although Kilpatrick et al .…”
Section: Discussionmentioning
confidence: 99%
“…These results are in contrast to virally expressed VGLUT3, which was exclusively in 100% of the inner HCs (Akil et al , ). Considering that other virally expressed exogenous proteins, including GFP (Akil et al , ; Wang et al , ) and connexin26 (Yu et al , ), all showed nonspecific expression, our results suggest that the cellular specificity achieved by VGLUT3 driven by a nonspecific promoter is an exception rather than a common phenomenon. The ectopic Kcnq1 expression demonstrated in this work also gave us an opportunity to investigate possible side effects of such expression outside the targeted cells.…”
Section: Discussionmentioning
confidence: 71%
“…A number of AAV serotypes and over 100 naturally occurring AAV variants have been isolated from adenovirus stocks or from human/nonhuman primate tissues. They display different cell tropisms (14), but there are some discrepancies in their reported transduction efficiencies and cell tropisms in the inner ear (26)(27)(28)(29). We thus investigated the ability of several AAV vectors to transduce the inner ear hair cells.…”
Section: Viral Cdna Transfer Restores Sans Expression and Targeting Imentioning
confidence: 99%